Extraction, analysis, and occurrence of per- and polyfluoroalkyl substances (PFAS) in wastewater and after municipal biosolids land application to determine agricultural loading - Caniglia, Justin; Snow, Daniel D.; Messer, Tiffany; Bartelt-Hunt, Shannon (Frontiers in Water, 2022)
Given the ubiquitous detection of per- and polyfluoroalkyl substances (PFAS) within numerous soil and water environmental compartments, there is a need for simplified methodologies for extracting water, solids, and plant tissue for these substances. This study provides details of several extraction methods and demonstrates the use of polar organic chemical integrative samplers (POCIS) in monitoring these compounds in a wastewater environment. Validated extraction procedures help characterize occurrence and release of 18 PFAS in a midwestern wastewater treatment plant (WWTP), surface water, and after land application of biosolids to agricultural test plots. Of the compounds measured, 14 PFAS were detected at least at one sampling site or type. The average total (Σ PFAS) dissolved phase time-weighted average (TWA) concentration in wastewater influent, effluent and in the upstream and downstream effluent mixing zone (EMZ) sites in the receiving stream respectively were 27.9, 132, 37.7, and 71.4 ng L-1. Long-chain PFAS dominated most of the aqueous compartments, and perfluoroalkyl acids (PFAAs) occurred in the WWTP and receiving surface waters. Total Σ14 PFAS measured in municipal biosolids applied to soils were 22.9 ng g-1 dw with long-chain PFAS comprising 77.5% of the cumulative PFAS mass. Perfluorooctanesulfonic acid (PFOS) was the most abundant compound detected in biosolids at the highest concentration (9.40 ng g-1 dw). Accumulation in WWTP biosolids was estimated to occur at a rate of 72.8 g day-1 dw based on the difference between influent and effluent time weighted average concentrations. PFAS were detected in both surface soil and runoff after land application of biosolids, but also in control plots consistent with background PFAS contamination. PFAS concentrations in surface runoff decreased over time from plots treated with biosolids. These results provide evidence of the introduction of PFAS to agroecosystems from wastewater effluent and land application of biosolids.